The Effect of Yttrium Addition on the Microstructure and Irradiation Hardening in V-4Cr-4Ti Alloy under Self-Ion Irradiation - Hongtai Luo; Fengfeng Luo; Yiheng Chen; Jiawei Wang; Qiuxiang Liu; Fang Li; Xiong Zhou; Liping Guo (Metals, 2021)
Microstructure and irradiation hardening of V-4Cr-4Ti alloys with different yttrium (Y) contents were studied by self-ion irradiation at 550 °C via TEM and nano-indentation test technology. The peak damage of the V-4Cr-4Ti-xY alloy (x = 0, 0.1, 0.5, and 1, wt.%) irradiated by 2.5 MeV self-ion (V2+) is 8 dpa. Dense dislocation loops were observed in all vanadium alloy samples after irradiation. With the increase of Y content, both average size and number density of dislocation loops using g = <110> near the pole [001] decreased, while the irradiation hardness increment first decreased and then increased. In order to better reduce the irradiation hardening, it is considered that the addition of 0.1 wt.% Y in V-4Cr-4Ti alloy is reasonable.